First Report of canker and branch dieback of sweet cherry trees caused by Calosphaeria pulchella in Chile - Auger, Jaime (Plant disease, 2020)
In Chile, the 2019-2020 sweet cherry season yielded 228,548 t, produced on 38,392 hectares and an average annual crop value about US$1.6 billion (http://www.iqonsulting.com/yb/). Between autumn 2019 and summer of 2020, branch and limbs dieback symptoms were observed in two 12-year-old sweet cherry (Prunus avium L.) orchards located in the O'Higgins region (Chile Central Valley). Furthermore, other symptoms such as wilting leaves, cankers, bark cracking, emission of gum exudates and internal wood necrosis were detected on trees of "Bing", "Santina" and "Sweetheart" cultivars (Cainelli et al. 2017). Wood fragments from symptomatic branches were surface sterilized with 95% ethanol, flaming and placed onto potato dextrose agar (PDA) amended with 0.5 g liter-1 of streptomycin sulfate (Berbegal et al. 2014). After 7 days of incubation at 25°C, pink to red colonies with white margins were isolated. Each isolate was characterized by having hyaline and oblong-ellipsoidal conidia of 5.76 ± 0.88 × 1.76 ± 0.36 μm (n=100) (Trouillas et al. 2012). According to these morphological features, the fungus was identified as Calosphaeria pulchella (Pers.: Fr.) J. Schröt (anamorph Calosphaeriosphora pulchella Réblová,L. Mostert, W. Gams & Crous) (Réblová et al. 2004). ITS (Internal Transcribed Spacer region of the rDNA) sequence comparison using BLAST analysis revealed a 99.48% identity and 100% query coverage between C. pulchella sequence HM237297 and the Chilean isolates. Moreover, the Chilean isolates were confirmed by means of phylogenetic analysis using ITS sequences of C. pulchella available in GenBank database. The maximum-parsimony phylogenetic tree supported the cluster analysis of the Chilean C. pulchella isolates with those obtained in other regions of the world with a bootstrap value of 95% (Berbegal et al. 2014; Trouillas et al. 2012). The Chilean ITS sequences were deposited into GenBank (MT378444 to MT378447). Two-year-old sweet cherry trees cv. Bing were inoculated with the Chilean isolates. Six trees were used as replicates. To accomplish this goal, two punctures of 5mm diameter were made in two branches per tree with a cork borer and a plug of mycelium from 7-day-old colonies was laid on the wound mycelium side down. Six trees were inoculated with sterile agar plugs. Every puncture was sealed with petroleum jelly and wrapped with parafilm. Four months after inoculation, the vascular streaking developing from the inoculated wounds was measured. The average lesion lengths on inoculated and non-inoculated shoots were 43.79 and 21.79 mm, respectively, which were significantly different according LSD Fisher test (p<0.05). C. pulchella was recovered from all the inoculated branches. No fungus was isolated from the controls, confirming Koch's postulates (Trouillas et al. 2012). To our knowledge this is the first report of C. pulchella causing canker and branch dieback in sweet cherry trees in Chile. This new disease represents a serious threat to the Chilean cherry industry, and further research on disease control is needed